South Korean Hurry-Hurry (빨리 빨리) COVID-19 Strategy: Privacy Concern, No-Lockdown, and Discriminations - Annisa Pratamasari (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Unair, 2020)
South Korea has been hailed as one of the most successful countries in containing the spread of the novel coronavirus, COVID-19, within a relatively short period. Some argued that East Asian countries’ success could be attributed to Confucianist culture, to which I disagree. In this paper, I shall describe in details how Korean government managed to curb the Covid-19 spread with the combination of epidemiological investigation, advanced technology, and haste (빨리 빨리) culture, leading to a hurry-hurry strategy unique to South Korea. I would also outline some social impacts on LGBT-Q communities and the exclusion of foreign residents in South Korean pandemic efforts.Keywords: South Korea, COVID-19, hurry-hurry strategy.Korea Selatan dipuja sebagai salah satu negara tersukses dalam membendung penyebaran coronavirus, COVID-19, dalam waktu yang terbilang singkat. Beberapa tulisan berargumen bahwa kesuksesan negara-negara Asia Timur merupakan berkat nilai-nilai Konfusius mereka, yang tidak penulis setujui. Di artikel ini, penulis akan mendeskripsikan secara detail bagaimana pemerintah Korea mampu membendung penyebaran COVID-19 melalui kombinasi investigasi epidemiologis, teknologi mutakhir, dan budaya buru-buru (빨리 빨리) mereka, yang berkontribusi terhadap ‘hurry-hurry strategy’ unik milik Korea Selatan. Selain itu, penulis juga akan menjabarkan dampak sosial bagi komunitas LGBT-Q dan ekslusi penduduk asing dalam kebijakan penanggulangan pandemik di Korea Selatan.Kata-kata kunci: Korea Selatan, COVID-19, hurry-hurry strategy.